Trust and risk propensity: a case study from rural Vietnam - Yong, Yanminn (Nanyang Technological University, 2022)
Trust levels, identified by some scholars to be a potential determinant of risky behaviours, may affect risk attitudes and behaviours within a rural population. This paper examines the effect of trust levels on households’ risk propensities in rural Vietnam. A two-period panel dataset comprising surveyed information from rural households in Vietnam was analysed using Ordinary Least Squares (OLS), Fixed-effects (FE), and the Instrumental Variable & Two-stage least squares (IV-2SLS) frameworks. In an attempt to mitigate the endogeneity issue, an instrument – communal coverage of the network of water drinking distribution – was adopted to proxy households’ trust levels. The OLS, FE, and IV-2SLS estimates show significant positive correlation between the effect of trust and risk propensities. Specifically, the FE estimates indicate that a one standard deviation increase in trust levels result in a 15% increase in the number of lotteries offers accepted by the households. These results are robust to the use of different estimation models and different dataset sizes. Apart from contributing empirical insights to the two literature bodies concerning the trust-risk synergy as well as rural development, our findings also have material policy implication, that is, more efforts should be channelled to improving the various agents’ trustworthiness amongst rural households.